2020
DOI: 10.21037/tgh.2020.03.02
|View full text |Cite
|
Sign up to set email alerts
|

Approach to prevention of non-alcoholic fatty liver disease after liver transplantation

Abstract: Non-alcoholic fatty liver disease (NAFLD) is one of the most common causes of liver disease and non-alcoholic steatohepatitis (NASH) related cirrhosis is third common indication for liver transplantation (LT). Patients who have NASH related cirrhosis and are candidates for LT often have multiple comorbidities.These comorbidities need to be addressed before and after transplantation as it affects overall survival. Like hepatitis B, hepatitis C, primary biliary cirrhosis, autoimmune hepatitis which recurs after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 39 publications
0
13
0
1
Order By: Relevance
“…The development of post-LT metabolic syndrome is frequent[ 56 ]. In addition to lingering pre-LT risk factors, there is an increase in post-LT risks due to immunosuppression with corticosteroids and CNI[ 57 ]. Moreover, it is expected that metabolic syndrome components after LT will continue to rise due to the increase of NASH/MAFLD as an indication for LT[ 31 - 33 , 58 ].…”
Section: Causes Of Renal Dysfunction In Ltmentioning
confidence: 99%
“…The development of post-LT metabolic syndrome is frequent[ 56 ]. In addition to lingering pre-LT risk factors, there is an increase in post-LT risks due to immunosuppression with corticosteroids and CNI[ 57 ]. Moreover, it is expected that metabolic syndrome components after LT will continue to rise due to the increase of NASH/MAFLD as an indication for LT[ 31 - 33 , 58 ].…”
Section: Causes Of Renal Dysfunction In Ltmentioning
confidence: 99%
“…Hepatic steatosis has been recognized as the hepatic manifestation of metabolic syndrome (MetS). LT resolves the complications of cirrhosis due to metabolic-associated steatohepatitis (MASH), but the metabolic risks persist and often can get aggravated by exposure to immunosuppressive therapy after LT[ 13 ]. Therefore, it is not surprising to expect a higher rate of recurrent graft steatosis after LT compared to that of de novo graft steatosis due to the underlying MetS and IR that initially led to cirrhosis[ 14 ].…”
Section: Epidemiologymentioning
confidence: 99%
“…The development of graft steatosis after LT is related to different factors: Recipient, environmental, genetic, and immunosuppressive factors[ 13 ]. A retrospective study by El Altrache et al [ 18 ] reported the association of recurrent graft steatosis with the occurrence of metabolic abnormalities after LT.…”
Section: Risk Factors/predictorsmentioning
confidence: 99%
See 2 more Smart Citations